101 Reasons to be a nurse - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
''I couldn’t give you five good reasons to be a nurse." These words were spoken by a Nursing Supervisor with over 20 years of experience as a dedicated healthcare provider committed to her profession and to her patients. Her message was clear and indicative of the frustrations felt by nurses everywhere. She spoke of the difficulties facing our profession, including inadequate staffing, patient ratios, compensation, employee morale, stress, and 'burn out.' Despite all this, my response to her statement was quick and heartfelt:  "Well, I can give you 100 reasons to be a nurse!" She ignited in me a flame that continues to burn, and 101 Reasons to be a Nurse was born.The nursing shortage is a global crisis anticipated to reach critical proportions and negatively impact the health and safety of patients and healthcare providers. Recent studies show a definitive link between the nursing shortage and negative patient outcomes. Factors that contribute to the growing global nursing shortage include an aging workforce, declining student enrollment, and an increased demand for nursing care due to the aging of the general population. Other contributing factors include nurses’ complaints of stress, low morale and poor working conditions, which create a perception of our profession as undesirable. Part of the answer may be simple. Change the message. The day-to-day challenges of staffing, hours, salary and work conditions are being addressed and recognized in the media on a national and global level. Numerous organizations, including private companies and government agencies, are reaching out to explore and seek solutions to the nursing shortage. But only we, as nurses, have the power to truly affect change. We must change the image and perception of nursing, and portray our field as it truly is. It is a profession as essential to life as breathing. Value who are you are, what you do, and why you do it. Breathe life back into yourself as you would a patient.My message in 101 Reasons to be a Nurse is simple. There is no other profession that can provide the opportunities, job satisfaction and personal rewards that nursing does. I challenge YOU to remember why YOU chose to enter the field of nursing. It was not money, job security or because you thought it would be easy. You chose to be a part of a profession that is second to none. YOU are the backbone of healthcare, the foundation and heart of this business of life. YOU are the difference in healthcare. Believe it! Say it! I have always considered myself "just a nurse.” The joys, the sorrows, the lives that have touched me over 30 years have helped shape who I am today. I am proud to say I am still just a nurse, one with a passion and burning desire to eradicate the negativity surrounding our profession. Through my book, I have found my voice. I will not be silent. Hear my message: You are the best you can be -- you are a nurse!